2020
DOI: 10.21273/hortsci14661-19
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Rare Earth Elements on Growth and Determination of Secondary Metabolites under In Vitro Conditions in Salvia miltiorrhiza

Abstract: Salvia miltiorrhiza, known as danshen, is one of most valued medicinal plants in China. Although it has been cultivated since ancient times, an optimal culture system needs to be standardized for this important species. Here, we explored the phytochemical properties of S. miltiorrhiza with the treatments of rare earth elements (REEs) to develop an optimal tissue culture system. Four-week-old in vitro-grown S. miltiorrhiza Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 29 publications
(43 reference statements)
2
7
0
Order By: Relevance
“…REEs have a synergistic effect with a burdock fructo-oligosaccharide, which constitutes an important energy source during germination [46]. Similarly, chlorophyll content, antioxidant enzyme activity, and secondary metabolites can be enhanced in response to REEs, including Ce [4]. These responses may explain, at least in part, the results observed in our study.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…REEs have a synergistic effect with a burdock fructo-oligosaccharide, which constitutes an important energy source during germination [46]. Similarly, chlorophyll content, antioxidant enzyme activity, and secondary metabolites can be enhanced in response to REEs, including Ce [4]. These responses may explain, at least in part, the results observed in our study.…”
Section: Discussionsupporting
confidence: 62%
“…Currently, REEs are pivotal components of modern industries and play key roles in medicine, chemistry, agriculture and livestock farming [2]. In plant biology, REEs may improve photosynthesis, biomass accumulation, and primary and secondary metabolism, as well as the activity of numerous enzymes involved in vital physiological processes such as growth, development and responses to stress [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, excessive concentrations adversely alter photosynthesis and antioxidant activity. The highly augmented carotenoid levels are consistent with research findings that suggest that rare-earth elements at low concentrations promote chlorophyll content and the rate of phosphorylation (Fan et al, 2020). Malondialdehyde (MDA) is a lipid peroxidation marker (Tounekti et al, 2011).…”
Section: Discussionsupporting
confidence: 84%
“…A recent study has also reported T. officinale as a good bioindicator of REE (Borowiak et al, 2018). Some of the elements are even found to enhance plant growth, for example the medicinal plant Salvia miltiorrhiza showed enhanced plant growth and a higher secondary metabolite content in plant parts when grown in the presence of 100 mM praseodymium (Pr) (Fan et al, 2020). Elongation in root structure and enhanced photosynthetic activity were also observed.…”
Section: Bioindicator Plantsmentioning
confidence: 95%